Initial Canadian Experience of Prostate Artery Embolization for Symptomatic Benign Prostatic Hyperplasia: Midterm Outcomes. Issue 4 (November 2021) - Patel, Neeral R.; Elterman, Dean S.; Thulasidasan, Narayanan; Altman, Rachel; Tai, Elizabeth; Zener, Rebecca; Stella, Steffan F.; Annamalai, Ganesan; Mafeld, Sebastian; Simons, Martin E.
Introduction: This study aimed to assess the midterm outcomes and safety of prostate artery embolization (PAE) for the treatment of benign prostatic hyperplasia (BPH). Methods: A single-center, retrospective review of PAE performed for BPH was performed. Validated International Prostate Symptom Score (IPSS), quality of life (QoL) index, and International Index for Erectile Function (IIEF-5) questionnaires were completed at baseline and at least 12 months post-procedure. Prostate imaging was performed preprocedure as well as 3 months and 12 months post-procedure to assess prostate volume (PV). Uroflowmetry was also performed at baseline and 12 months post-procedure to assess urine flow rate (Qmax ) and post-void residual (PVR) volume. Adverse events were graded according to Society of Interventional Radiology (SIR) guidelines. Results: Eighty male patients underwent the PAE procedure (mean age 69 years). Prostate volume decreased significantly from a mean volume 156 to 107 mL after 12 months post-procedure, commensurate with a mean reduction of 27.5% ( P < .05). Significant improvements were seen in IPSS (21.8 vs 10.5) and QoL (4.5 vs 2.0) from baseline to 12 months post-procedure ( P < .05). There was no significant change in IIEF-5 score. There was a significant reduction in PVR (202 vs 105 mL) and improvement in Qmax (5.9 vs 10.0 mL/s) between baseline and 12 months post-procedure ( P < .05). No major complications occurred; 4 minor complications occurred (SIR grade A or B). Conclusion: Prostate artery embolization achieved a clinically and statistically significant prostate volume reduction, symptom and QoL improvement, and enhanced uroflowmetry parameters in patients with BPH.